(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article deals with folk Karakalpak traditions and beliefs in the field of relics of nature. The cultural relationship of the Karakalpak people with other peoples of Central Asia and Kazakhstan in the field of traditional folk cultures is also considered.